Effective mechanisms of water purification for nitrogen-modified attapulgite, volcanic rock, and combined exogenous microorganisms - Zheng, Yao; Wang, Yuqin; Yang, Xiaoxi; Gao, Jiancao; Xu, Gangchun; Yuan, Julin (Frontiers in Microbiology, 2022)
The study tested the water purification mechanism of the combination of microorganisms and purification materials via characteristic, enzymatic, and metagenomics methods. At 48 h, the removal rates of total nitrogen, total phosphorous, and Mn chemical oxygen demand in the combination group were 46.91, 50.93, and 65.08%, respectively. The alkaline phosphatase (AKP) activity increased during all times tested in the volcanic rock, Al@TCAP, and exogenous microorganism groups, while the organophosphorus hydrolase (OPH), dehydrogenase (DHO), and microbial nitrite reductase (NAR) activities increased at 36-48, 6-24, and 36-48 h, respectively. However, the tested activities only increased in the combination groups at 48 h. Al@TCAP exhibits a weak microbial loading capacity, and the Al@TCAP removal is primarily attributed to adsorption. The volcanic rock has a sufficient ability to load microorganisms, and the organisms primarily perform the removal for improved water quality. The predominant genera Pirellulaceae and Polynucleobacter served as the sensitive biomarkers for the treatment at 24, 36-48 h. Al@TCAP increased the expression of Planctomycetes and Actinobacteria, while volcanic rock increased and decreased the expression of Planctomycetes and Proteobacteria. The growth of Planctomycetes and the denitrification reaction were promoted by Al@TCAP and the exogenous microorganisms. The purification material addition group decreased the expression of Hyaloraphidium, Chytridiomycetes (especially Hyaloraphidium), and Monoblepharidomycetes and increased at 36-48 h, respectively. Ascomycota, Basidiomycota, and Kickxellomycota increased in group E, which enhanced the nitrogen cycle through microbial enzyme activities, and the growth of the genus Aspergillus enhanced the phosphorous purification effect.